Peningkatan Kemampuan Baca Tulis Pegon bagi Guru dan Santri Di TPQ dan Madin Baiturrohman Sugihan Duren Sawahan Nganjuk - Juni Iswanto; Asichul In'am (Janaka, Jurnal Pengabdian Masyarakat, 2021)
Based on the problems, potentials, and assets of the Sugihan Duren Sawahan hamlet, the dedication was focused on the teacher and student assistance program in writing pegon (meaning gandul). This activity aims to develop the potential of human resources related to teacher and student training in pegon writing at TPA and Madin Baiturrohman. This program is applied to assisted objects due to the lack of personnel and training and learning related to the improvement of similar competencies, besides that it is also asked by the Board of Pesantren to provide direction and input related to pegon writing training. Various obstacles are faced by the assisted objects, starting from the lack of teachers, low student enthusiasm, the unorganized curriculum being taught, and various other problems, especially in understanding the contents of the Yellow Book and learning to write the Koran at TPA Baitur Rohman Sugihan Duren Sawahan Nganjuk. The existence of this program is expected to improve the ability of students in writing pegon so that they can easily study and deepen religious materials based on the yellow book.